Uji Efek Antipiretik Ekstrak Etanol Buah Wualae (Etlingera elatior (Jack) R.M. Smith) Terhadap Mencit Jantan (Mus musculus L.) Galur Balb/C - Malik, Fadhliyah; Ningsi, Andryani; Bafadal, Mentarry; Saktiani, Dwi Nur; Wahyuni, Wahyuni (Fakultas Farmasi Universitas Halu Oleo, 2018)
Wualae (Etlingera elatior (Jack) R.M. Smith) empirically been used by people to treat diseases and as food. This research was carried to determine the antipyretic activity of ethanol extracts of Wualae (Etlingera elatior (Jack) R.M. Smith) fruit on male mice (Mus musculus L) Balb/c along with ratio the effects of ethanol extracts of fruit Wualae with paracetamol as a antipyretic. Ethanol extracts of fruit Wualae obtained by maceration method using ethanol 96%. Male mice divided into 6 groups i.e: negative control (Na.CMC), positive control, and the treatment group (ethanol extracts of fruit Wualae 100 mg/KgBW, 200 mg/KgBW, 300 mg/KgBW, dan 400 mg/KgBW). Antipyretic activity tested by using DPT vaccine (Diphtheria Tetanus Pertussis) 0.1 cc intraperitoneally as an inducer and paracetamol 500 mg as a positive control. Temperature measurement determined for 3 hours with a 30 minutes interval. Data analysis was performed by Kruskal Wallis statistical analysis and continued with Mann-Whitney test. The results showed that the effects of ethanol extracts of wualae fruit at dose of 400 mg/KgBW has antipyretic effects with a total decrease of temperature was 1,237oC.Keywords: antipyretic, fever, Etlingera elatior, wualae, mice